COMPARATIVE EFFICACY OF POLYPROPYLENE MESH AND JEJUNAL GRAFT FOR THE REPAIR OF ABDOMINAL WALL DEFECT IN DOGS - M. A. Khan; T. Hamid; A. K. Mahmood; U. Farooq; S. S. Ahmad; M. K. Shahzad (Journal of Animal and Plant Sciences, 2008)
Abdomen is a very delicate part of the body. It is prone to trauma and clinical disorders like malignant soft tissues tumors, abdominal hernias are quite common in both young and mature dogs. In massive abdominal wall defects, the use of graft becomes mandatory to achieve desirable results Different techniques have been performed to overcome this challenge. The present study was conducted to find out the efficacy of two different techniques for repair of abdominal wall defects. Ten mongrel dogs of both sexes were divided into two equal groups viz. A and B. In group A, abdominal wall defect was repaired by polypropylene mesh and in group B it was repaired by autogenous jejunal graft with intact blood supply. In group A, all dogs were survived and did not show any herniation through operative site. Contrarily, in group B, several postoperative complications were observed. The results of the study indicated that the polypropylene mesh graft is better choice over the autogenous jejunal graft for repair of abdominal wall defects in dogs.
Keywords: Mongrel dogs; abdominal wall defect; polypropylene graft; jejunal graft; postoperative complications